C69 EFFECTIVENESS AND SAFETY OF DISTINCT ANTIPLATELET REGIMENS AFTER TRANSCATHETER LEFT ATRIALE APPENDAGE OCCLUSION: A SINGLE CENTER REAL–WORLD EXPERIENCE. (18th May 2022) - Gurgoglione, F; Barocelli, F; Vignali, L; Maini, A; Solinas, E; Tadonio, I; Benatti, G; Coli, S; Pelà, G; Grassi, F; Lina, D; Niccoli, G; et al.
Abstract: Transcatheter left atrial appendage occlusion (LAAO) has emerged as a reliable tool to prevent thromboembolic events, in particular ischemic stroke, in patients with atrial fibrillation (AF) in the absence of mitral stenosis/valve prosthesis and contraindication to oral anticoagulation (OAC). Antiplatelet therapy (APT) is required after device implantation to prevent device–related thrombus (DRT). Previous studies provided conflicting results on the optimal APT regimen after LAAO. Thus, herein we aimed at assessing the comparative effectiveness and safety of distinct APT regimens. We conducted a real–world single–center observational study including consecutive AF patients that underwent LAAO at the University Hospital of Parma between October 2010 and June 2021. Clinical follow–up included all successfully implanted patients. Primary endpoint was net efficacy outcome, a composite of any ischemic or hemorrhagic event. Secondary endpoints were ischemic (any of the following: ischemic stroke, transient ischemic attack [TIA], DRT, systemic embolism) and hemorrhagic (major [≥3] bleedings according to Bleeding Academic Research Consortium [BARC] classification) complications alone. We enrolled a total of 130 patients (median age 77.0 [72.7;81.0] years; 78 [60.0%] men). History of hemorrhagic stroke in OAC (74 [56.9%]) was the main indication for LAAO. Technical procedure success was achieved in 123 (94.6%) patients. According to multidisciplinary team evaluation, immediately after LAAO, 39 (31.7%) patients received short (≤ 1 month)–dual APT (DAPT) consisting of cardioaspirin and clopidogrel, 35 (28.5%) long (>1, ≤12 months)–DAPT and 49 (39.8%) single APT (SAPT). At a median follow–up of 32 months, the incidence of primary endpoint was significantly lower in short–DAPT group (3 [7.7%] vs. 7 [20.0%] in long–DAPT vs. 14 [28.6%] in SAPT, p = 0.049], mainly driven by a lower occurrence of bleeding endpoint (0 [0.0] vs. 4 [11.4%] in long–DAPT vs. 9 [18.4%] in SAPT, p = 0.020) without differences in the incidence of ischemic endpoint (p = 0.916). Finally, comparison of the Kaplan–Meier curves showed that short–DAPT group had a higher primary endpoint–free survival (p = 0.015) compared to the others. In summary, our study highlighted that short (≤ 1 month)–DAPT regimen after LAAO is associated with better outcomes, mainly driven by reduction of major bleedings. Strong evidences arising from randomized trials are warranted to support these findings.